LAMIKRO APPLICATION IN PREPARING MSME FINANCIAL REPORTS BASED ON SAK EMKM - Dwijayanti, Ni Made Ayu; Lasmini, Ni Nengah; Ardina, Cening; Yintayani, Ni Nyoman (Jurnal Akuntansi dan Keuangan (JAK), 2025)
This study aims to determine the effectiveness of the LAMIKRO Digital Application in preparing SAK EMKM-based financial statements at Salsabila Leather Bags. This type of research uses a qualitative method using a Field Research approach. Data is obtained from primary data sources and secondary data. Data analysis is done through data collection, data reduction, data presentation and conclusion drawing. The results of this study prove that leather bag MSMEs consider financial reports difficult, MSME owners do not have web-based or android-based accounting applications and still make inconsistent financial records. This research contributes to helping MSMEs prepare financial reports according to standards by using the LAMIKRO application. The use of the LAMIKRO application can help MSMEs to make financial reports based on standards, so that MSMEs can find out the financial position report, income statement, and notes to financial statements in real time. The results of this study also indicate a high commitment from MSME actors to use the LAMIKRO application sustainably.